Proactive Service Recovery Performance in Emerging (vs. Developed) Market-Based Firms: The Role of Clients’ Cultural Orientation - Bakhsh , Naghmeh Nik; Hollebeek, Linda D.; Riivits-Arkonsuo, Iivi; Clark, Moira K.; Casas, Ramunas (Organizations and Markets in Emerging Economies, 2023)
Though service recovery plays a key role in industrial clients’ post-recovery supplier evaluations, the impact of customers’ cultural orientation on the effectiveness of supplier-instigated proactive recovery (i.e., a supplier’s recovery efforts before clients notice/complain) remains tenuous, particularly in emerging (vs. developed) markets. Addressing this gap, we develop a model that examines (a) the moderating role of clients’ cultural orientation on the association of supplier-instigated proactive recovery and client-perceived recovery-related justice, and (b) the impact of customer-perceived justice on relationship quality in the emerging (vs. developed) market context. To test the model, we deploy a cross-cultural scenario-based experiment using 117 Danish industrial clients (i.e., developed market) and 109 Iranian industrial clients (i.e., emerging market). The results suggest that customers’ cultural orientation partially moderates the relationship of suppliers’ proactive recovery and customer-perceived justice, in turn boosting relationship quality in the emerging/developed market context.